Efektifitas Konsumsi Telor dan Tablet FE Terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri Yang Mengalami Anemia di Puskesmas Ciputat Tahun 2023 - Siti Maysaropah; Ernita Prima Noviyani; Uci Ciptiasrini (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Anemia in adolescent girls is a common health problem that can affect their quality of life. This study aims to analyze the effectiveness of consuming eggs and iron (Fe) tablets in increasing hemoglobin levels in adolescent girls with anemia at Puskesmas Ciputat in 2023. This research employs a quantitative design with a quasi-experimental approach and a One Group Pretest and Posttest method. The sample consisted of 60 adolescent girls, divided into two groups: the intervention group (30 participants) consumed 1 boiled egg and an Fe tablet daily for 14 days, while the control group (30 participants) only consumed Fe tablets. Hemoglobin levels were measured before and after the intervention. The results showed a significant increase in hemoglobin levels in the intervention group compared to the control group. The implications of this study emphasize the importance of combining egg consumption with Fe tablets as a strategy to address anemia in adolescent girls, which could be an alternative solution for public health programs at Puskesmas Ciputat